2006
DOI: 10.1016/j.chembiol.2006.03.009
|View full text |Cite
|
Sign up to set email alerts
|

Mimicking Helical Antibacterial Peptides with Nonpeptidic Folding Oligomers

Abstract: Unnatural oligomeric scaffolds designed to adopt defined secondary structures (e.g., helices), while retaining the chemical diversity of amino acid side chains, are of practical value to elaborate functional mimetics of bioactive alpha-polypeptides. Enantiopure N,N'-linked oligoureas as short as seven residues long have been previously shown to fold into a stable helical structure, stabilized by 12- and 14-membered H-bonded rings. We now report that eight-residue oligoureas designed to mimic globally amphiphil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
128
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 123 publications
(131 citation statements)
references
References 38 publications
2
128
0
Order By: Relevance
“…56 In the area of modifications of natural products by combinatorial methods to produce entirely different compounds that may bear little if any resemblance to the original, but are legitimately assignable to the "NM" category, citations are given in previous reviews. 3,[57][58][59][60][61][62][63][64] In addition, one should consult the recent reports from Waldmann's group 65,66 and those by Ganesan, 67 Shang and Tan, 68 Constantino, 69 and Violette et al 70 on the use of privileged structures as skeletons around which to build libraries. Another paper of interest in this regard is the editorial by Macarron from GSK, 9 as this may be the first time where data from industry on the results of HTS screens of combichem libraries versus potential targets were reported with a discussion of lead discovery rates.…”
Section: Resultsmentioning
confidence: 99%
“…56 In the area of modifications of natural products by combinatorial methods to produce entirely different compounds that may bear little if any resemblance to the original, but are legitimately assignable to the "NM" category, citations are given in previous reviews. 3,[57][58][59][60][61][62][63][64] In addition, one should consult the recent reports from Waldmann's group 65,66 and those by Ganesan, 67 Shang and Tan, 68 Constantino, 69 and Violette et al 70 on the use of privileged structures as skeletons around which to build libraries. Another paper of interest in this regard is the editorial by Macarron from GSK, 9 as this may be the first time where data from industry on the results of HTS screens of combichem libraries versus potential targets were reported with a discussion of lead discovery rates.…”
Section: Resultsmentioning
confidence: 99%
“…Based on their work, several different helical peptides using β-peptides or α/β-peptides have been developed [71]. In addition to the work of Patch and Barron [72], who designed amphiphilic, helical peptoids of antibacterial N-substituted glycine oligomers [72], Violette et al [73] investigated antimicrobial foldamers with a urea backbone. It was reported that electrical charge, facial amphiphilicity, and a hydrophobic/hydrophilic balance are typically important factors in designing nontoxic antimicrobial compounds.…”
Section: Bioactive Oligopeptidesmentioning
confidence: 99%
“…1,2 Bactericidal peptidomimetics comprised of unnatural amino acids were thereby developed to circumvent the drawbacks of AMPs, which are protease-resistant and of improved bioavailability. 5 In recent years, several peptidomimetic analogues of AMPs, such as β-peptides, 6−9 arylamides, 10,11 and peptoids, 3,12,13 have received significant research interest.…”
mentioning
confidence: 99%
“…5 In recent years, several peptidomimetic analogues of AMPs, such as β-peptides, 6−9 arylamides, 10,11 and peptoids, 3,12,13 have received significant research interest.…”
mentioning
confidence: 99%